Predictors of thoracic and lumbar spine injuries in patients with TBI: A nationwide analysis. Issue 3 (March 2022) - Hauser, Blake M.; McNulty, John; Zaki, Mark M.; Gupta, Saksham; Cote, David J.; Bernstock, Joshua D.; Lu, Yi; Chi, John H.; Groff, Michael W.; Khawaja, Ayaz M.; Smith, Timothy R.; Zaidi, Hasan A.
Abstract: Objective: Cervical spine injury screening is common practice for traumatic brain injury (TBI) patients. However, risk factors for concomitant thoracolumbar trauma remain unknown. We characterized epidemiology and clinical risk for concomitant thoracolumbar trauma in TBI. Methods: We conducted a multi-center, retrospective cohort analysis of TBI patients in the National Trauma Data Bank from 2011-2014 using multivariable logistic regression. Results: Out of 768, 718 TBIs, 46, 654 (6.1%) and 42, 810 (5.6%) patients were diagnosed with thoracic and lumbar spine fractures, respectively. Only 11% of thoracic and 7% of lumbar spine fracture patients had an accompanying spinal cord injury at any level. The most common mechanism of injury was motor vehicle accident (67% of thoracic and 71% and lumbar fractures). Predictors for both thoracic and lumbar fractures included moderate (thoracic: OR 1.26, 95%CI 1.21-1.31; lumbar: OR 1.13, 95%CI 1.08-1.18) and severe Glasgow Coma Scale (GCS) score (OR 1.71, 95%CI 1.67-1.75; OR 1.17, 95%CI 1.13-1.20) compared to mild; epidural hematoma (OR 1.36, 95%CI 1.28-1.44; OR 1.1, 95%CI 1.04-1.19); lower extremity injury (OR 1.38, 95%CI 1.35-1.41; OR 2.50, 95%CI 2.45-2.55); upper extremity injury (OR 2.19, 95%CI 2.14-2.23; OR 1.15, 95%CI 1.13-1.18); smoking (OR 1.09, 95%CI 1.06-1.12; OR 1.12, 95%CI 1.09-1.15); and obesity (OR 1.39, 95%CI 1.34-1.45; OR 1.29, 95%CI 1.24-1.35). Thoracic injuries (OR 4.45; 95% CI 4.35-4.55) predicted lumbar fractures, while abdominal injuries (OR 2.02; 95% CI 1.97-2.07) predicted thoracic fractures. Conclusions: We identified GCS, smoking, upper and lower extremity injuries, and obesity as common risk factors for thoracic and lumbar spinal fractures in TBI.